Synthesis and characterization of branched gold nanoparticles - Beynik, T.G.; Matveevskaya, N.A.; Dobrotvorskaya, M.V.; Garbuz, A.S.; Kosyanov, D.Yu.; Vovna, V.I.; Vornovskikh, A.A.; Bogatyrenko, S.I. (Functional Materials, 2017)
In this paper we demonstrate obtaining and properties of gold nanostars and nanoflowers with average size in the range of 50 to 70 nm and the size dispersion < 20 %. Transmission electron microscopy and photoelectron spectroscopy were used to study the composition and structure obtained Au nanoparticles, optical properties their colloidal solutions were studied."